Juvenile Polyposis Syndrome in a Young Patient: A Rare Case Report - Agrawal, Yamuna; Shah, Rajan; Joshi, Brikh Raj; Kattel, Vivek (Birat Journal of Health Sciences, 2018)
Juvenile polyposis syndrome prevalence is 1 in 16,000 to 1 in 100,000 which usually present at the age of 20 years. The tumor is likely to change into malignant condition in 20% of cases. Here we present this rare syndrome in a 16-year boy. BJHS 2018;3(2)6:492-494.